ASSESSING THE POTENTIAL OF ELECTRIC MOBILITY FOR LOW CARBON TRANSIT TOURISM: EVIDENCE FROM THE BELGRADE-ZLATIBOR CORRIDOR - Vranešević, Branko; Vujko, Aleksandra; Knežević, Miroslav (The European Journal of Applied Economics, 2026)
Transit tourism in mountainous regions generates a considerable carbon footprint due to the dominant use of internal combustion vehicles, particularly along intensively used routes such as the Belgrade-Zlatibor corridor. Although electric mobility offers the potential to reduce transport-related emissions, its relevance for Serbia’s transit tourism has not been systematically examined. This study addresses this gap by integrating an assessment of the existing charging infrastructure, an on-site survey of travelers conducted on Zlatibor (N=500), and a comparison of electric and conventional vehicles using established life cycle assessment (LCA) data. The aim is to evaluate the extent to which electric mobility can support a transition toward lower-carbon transit tourism along this corridor. The findings show that adventure- and nature-based activities represent the primary motivation for travel, increasing the importance of sustainable transport solutions in environmentally sensitive mountain destinations. Survey results further indicate that more than half of respondents would be willing to use electric vehicles if charging infrastructure were more accessible and spatially distributed along the route. In line with international evidence, established LCA data consistently show significantly lower lifecycle CO₂ emissions for electric vehicles relative to conventional vehicles, depending on the energy mix and vehicle segment. Overall, the study highlights electric mobility as a feasible pathway for reducing transit-tourism-related emissions and strengthening destination sustainability planning.